First language interference on EFL learners’ speaking ability at the higher education level - Panjaitan, Rosinta; Seinsiani, Izzati Gemi (ELT Forum: Journal of English Language Teaching, 2025)
This research examines the influence of first language (L1) interference on the speaking ability of Indonesian EFL learners at the higher education level, focusing on English Education students. Using a mixed method approach, data were gathered through questionnaires (closed-ended and open-ended) and semi-structured interviews with intermediate-level learners in English. The findings identify two dominant forms of L1 interference: grammatical and phonological. Grammatical interference involves the transfer of Indonesian sentence structures and tense usage into English, while phonological interference appears in the mispronunciation of unfamiliar English sounds. Four key factors contribute to this interference: linguistic background, proficiency level, psychological barriers, and learning strategies. The interference significantly hinders both accuracy and fluency, often due to mental translation habits, lack of confidence, and overreliance on grammar-based instruction. The study concludes that L1 interference is a complex issue requiring communicative, confidence-oriented teaching methods and greater exposure to authentic English use. This insight offers practical implications such as the implementation of short lessons that give EFL students space to study or practice without pressure so that they can improve their English as a foreign language skill.